Implikasi Teologis Makna Peristiwa Pentakosta Dalam Kisah Para Rasul 2: 1-13 - Daido Tri Sampurna Lumbanraja (Institut Agama Kristen Negeri Palangka Raya, 2021)
Naturally the discussion about the Spirit leads to the book of Acts which is the basis of the Baptism of the Holy Spirit by the Pentecostal school. As Pentecostalism developed, advocates emerged as people who were trained theologically, so that the discussion became moreweighty with the consensus that the interpretation of Acts must be carried out responsibly by applying correct hermeneutic principles. The author is interested in delving deeper into the text about the Holy Spirit from the events of Pentecost, namely Acts 2: 1-13, by applying hermeneutic principles in an exegetical study. Therefore, this article uses a type of literature research to support exegetical studies of the text of Acts 2: 1-13. The results obtained were in the form of interpretations of the Pentecost event, namely: the moment of the outpouring of the Holy Spirit as the fulfillment of God's promise and the moment of the outpouring was the fulfillment of the promise regarding the Power of the Holy Spirit as empowerment to become a witness of Jesus Christ. This article also includes the theological implications of today's Pentecost events. Secara natural diskusi mengenai Roh Kudus mengarah pada kitab Kisah Para Rasul yang menjadi landasan pengajaran tentang baptisan Roh Kudus oleh aliran Pentakosta. Seiring dengan berkembangnya aliran Pentakosta, bermunculan para advokat sebagai orang-orang yang terlatih secara teologis, sehingga diskusi menjadi lebih berbobot dengan adanya konsensus bahwa penafsiran Kisah Para Rasul, harus dilakukan secara bertanggung jawab dengan menerapkan prinsip-prinsip hermeneutik yang benar. Penulis tertarik untuk mengkaji lebih mendalam teks mengenai Roh Kudus dari peristiwa Pentakosta, yaitu Kisah Para Rasul 2: 1-13, dengan menerapkan prinsip-prinsip hermeneutik dalam suatu studi eksegesis. Dengan demikian artikel ini menggunakan jenis penelitian kepustakaan untuk mendukung studi eksegesis terhadap teks Kisah Para Rasul 2: 1-13. Hasil yang didapat berupa pemaknaan terhadap peristiwa Pentakosta, yaitu: momen pencurahan Roh Kudus sebagai penggenapan janji Allah dan momen pencurahan adalah penggenapan janji mengenai Kuasa Roh Kudus sebagai pemberdayaan untuk menjadi saksi Yesus Kristus. Artikel ini juga menyertakan implikasi teologis peristiwa Pentakosta pada masa sekarang.